Dipolar‐Distribution Cavity γ‐Fe2O3@C@α‐MnO2 Nanospindle with Broadened Microwave Absorption Bandwidth by Chemically Etching. Issue 5 (15th November 2016) - You, Wenbin; Bi, Han; She, Wen; Zhang, Yu; Che, Renchao
Abstract : Developing microwave absorption materials with ultrawide bandwidth and low density still remains a challenge, which restricts their actual application in electromagnetic signal anticontamination and defense stealth technology. Here a series of olive‐like γ‐Fe2 O3 @C core–shell spindles with different shell thickness and γ‐Fe2 O3 @C@α‐MnO2 spindles with different volumes of dipolar‐distribution cavities were successfully prepared. Both series of absorbers exhibit excellent absorption properties. The γ‐Fe2 O3 @C@α‐MnO2 spindle with controllable cavity volume exhibits an effective absorption (<−10 dB) bandwidth as wide as 9.2 GHz due to the chemically dipolar etching of the core. Reflection loss of the γ‐Fe2 O3 @C spindle reaches as high as −45 dB because of the optimized electromagnetic impedance balance between polymer shell and γ‐Fe2 O3 core. Intrinsic ferromagnetism of the anisotropy spindle is confirmed by electron holography. Strong coupling of magnetic flux stray lines between spindles is directly imaged. This unique morphology and facile etching technique might facilitate the study of core–shell type microwave absorbers. Abstract : Nanospindle‐like γ‐Fe2 O3 @C exhibiting excellent microwave absorption performance with a 2 mm coating layer is reported. After MnOn2 shell and dipolar‐distribution cavities are introduced, the effective bandwidth is broadened three times, which mainly arises from the loosely stacked α‐MnO2, dipolar‐distribution cavities, and its impedance balance between magnetic core and dielectric shells.